Energy retrofitting of existing buildings. Geometric-informative modelling and management - Giovanna A. Massari; Ambra Barbini; Elena Bernardini; Oscar Roman (Agathón, 2022)
In 2017 the company Fanti Legnami Srl launched the Renew-Wall research programme concerning a system of prefabricated timber-framed panels for energy performance improvement in existing buildings. In order to manage the complexity of the entire system, an integrated digital solution was developed to support the entire workflow, from design to production. The requirements of the digital solution are the ease of geometric and informative modelling in the design phase, the replicability and adaptability to different configurations and the transferability of information needed for production to the CAD-CAM system. This paper is aimed at illustrating the process of creating a library of BIM objects, as a key element of the integrated digital solution proposed for the management of the Renew-Wall system, describing the implementation and assessment of the procedures adopted.